Hematopathology - Hsi, Eric D. (Foundations in diagnostic pathology, 2018)
"With its highly templated, easy-to-use format and new information throughout, the third edition of Hematopathology, a volume in the Foundations in Diagnostic Pathology series, is an essential text for residents and pathologists. Throughout this practical reference, traditional morphologic diagnostic pathology is supplemented with clinical, immunohistochemical, and molecular genetic information"--Publisher's description